Menumbuhkan Service Loyalty Melalui Kualitas Pelayanan dan Pengelolaan Respon Emosi Konsumen pada Perusahaan Jasa - Y.Agung Adi Nugroho (Jurnal Manajemen Maranatha, 2006)
After the 1998 financial crisis in Asia a rapid growth of importance in service industries are taking on here in Indonesia. Therefore, the competitions of service businesses are becoming so tight that moves the companies to find an effective way to compete with their competitors. Services are one of the ways used by service industries as an edge to competitive business. Because of this, companies need to push into its limit in order to create service loyalty on their costumers to make costumers loyal. In this paper propose two factors that influence service loyalty. That is, service quality and managing emotional responses of the customers. The right service quality and the good management of emotional responds can build a strong service loyalty on their costumers. Finally, this paper also gives some practices or ways to improve service quality and management of emotional responses of the costumers for managerial practitioners.